Drivers of the Technology Adoption In Healthcare - Juliana Pascualote Lemos de Almeida; Josivania Silva Farias; Hervaldo Sampaio Carvalho (BBR: Brazilian Business Review)
This paper proposes a theoretical framework for the study of the diffusion of ICT in management and assistance services in healthcare and empirically verifies its applicability in studying adoption of technology in this area. There was a review of literature in the period 2004-2014. Based on this framework, the researchers verified empirically the applicability of organizational drivers proposed in the prior conditions, through a case study conducted by interviews with 13 managers of a Brazilian public hospital that is adopting a nursing prescription module. Through the content analysis, eight organizational drivers of the technology adoption were confirmed. For future research, it is relevant to verify the applicability of the organizational and individual drivers in the other phases of the framework organized according to Rogers (1983), as well as in the prior conditions, either by new case studies or by developing quantitative research instruments about the management process of technology adoption in organizations.